Influence of Structural Properties and Kinetic Constraints on Bacillus cereus Growth - Stecchini, Mara Lucia (American Society for Microbiology, 1998)
The influence of structural properties and kinetic constraints on the behavior of Bacillus cereus was investigated on agar media. Dimensional criteria were used to study the growth in bacterial colonies. The architecture of the agar gel as modified by the agar content was found to influence the colony size, and smaller colonies were observed on media containing 50 to 70 g of agar liter(−1). Except at low nutrient levels, colonies responded to nutrient gradients by decreasing in size the farther away they were from the nutrient source, and the decrease in colony size was influenced by the agar content. The diffusivities of glucose and a protein (insulin-like growth factor) were not affected by the gel architecture, suggesting that other factors, such as mechanical factors, could influence microbial growth in the agar systems used. Increasing the viscosity of the liquid phase of the agar media by adding polyvinylpyrrolidone resulted in a reduction in colony size. When the agar concentration was increased, the colony areas were not influenced by the viscosity of the system.